Evaluation of Anxiety and Fear of Anesthesia in Adults Undergoing Plastic Surgery with General Anesthesia - Fattahisaravi, Zeinabsadat (Asian Journal of Pharmaceutics (AJP), 2019)
Background: Pre-operative anxiety is a universal reaction experienced by patients who are admitted to hospitals for surgery. The present study aimed to assess the causes of anxiety and concerns about anesthesia in adults undergoing surgery. Methods: This cross-sectional study was conducted in Dastgheyb and Mother and Child Hospitals, Shiraz, in 2015. The data were collected using a demographic information form and a questionnaire including questions about the patients’ fears from anesthesia. Besides, the patients were required to score their anxiety from 0 to 10 in a specific form. An expert also measured the patients’ anxiety levels using a standard visual analog scale ranging from 0 to 10. Results: Totally, 72 of the 74 distributed questionnaires were completed (response rate: 97%). The results showed that the patients with more than 12 years of education, below 40 years of age, in the very important person section, and working in non-medical jobs, females, and single patients were more afraid of anesthesia. Besides, the results of Pearson’s correlation coefficient revealed a significant positive relationship between the anxiety scores reported by the patients and the expert (r = 0.813, P < 0.001). Conclusion: Identification of the causes of anxiety and concerns about anesthesia could be useful for designing specific preventive interventions to relieve patient suffering.